Accompanying Immunotherapy Using Cord Blood Cryopreserved Hemopoietic Cells to Treat Patients with Subacute Salpingo-Oophoritis - Grischenko, V. I.; Lazurenko, V. V.; Mertsalova, O. V.; Konko, D. I. (Problems of Cryobiology and Cryomedicine, 2004)
The transplantation effect of cord blood cryopreserved hemopoietic cells (â€œHemocordâ€ preparation) on the disease clinical manifestations and immunological indices in patients with subacute salpingo-oophoritis was studied. The results obtained testify to the fact, that the used â€œHemocordâ€ preparation together with the manifested clinical effect, causes an immune-modulating effect as well.